The Reliquary of Doña Magdalena de Ulloa (1525-1598) in the Collegiate Church of San Luis in Villagarcía de Campos (Valladolid): A New Perspective (BSAA arte, 2019)
This study analyses the origin of the reliquary chapel of the collegiate church in Villagarcía de Campos under the patronage of Doña Magdalena de Ulloa. The discovery of new documentation sheds light on the organisation of the exhibition as a whole and on the nature of the reliquaries with which it was endowed. These include three reliquary busts in gilded bronze and crystal glasses and chalices, of marked Flemish-German taste, now conserved in the Collegiate Museum.
Keywords: reliquary-chapel; reliquaries; Villagarcía de Campos (Valladolid); Magdalena de Ulloa; Jesuits